![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(2x\left(x-\frac{1}{7}\right)=0\)
⇒\(\left[{}\begin{matrix}2x=0\\x-\frac{1}{7}=0\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=0\\x=\frac{1}{7}\end{matrix}\right.\)
Vậy \(x=0;x=\frac{1}{7}\)
b) \(\frac{1}{2}x+\frac{3}{5}x=\frac{-33}{25}\\ \left(\frac{1}{2}+\frac{3}{5}\right)x=\frac{-33}{25}\\ \left(\frac{5}{10}+\frac{6}{10}\right)x=\frac{-33}{25}\\ \frac{11}{10}x=\frac{-33}{25}\\ x=\frac{-33}{25}:\frac{11}{10}\\ x=\frac{-33.10}{25.11}\\ x=\frac{-6}{5}\)
Vậy x = \(\frac{-6}{5}\)
c) \(\left(\frac{2}{3}x-\frac{4}{9}\right)\left(\frac{1}{2}+\frac{-3}{7}:x\right)=0\\ \Rightarrow\left[{}\begin{matrix}\frac{2}{3}x-\frac{4}{9}=0\\\frac{1}{2}+\frac{-3}{7}:x=0\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}\frac{2}{3}x=\frac{4}{9}\\\frac{-3}{7}:x=\frac{-1}{2}\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=\frac{4}{9}:\frac{2}{3}=\frac{4.3}{9.2}=\frac{2}{3}\\x=\frac{-3}{7}:\frac{-1}{2}=\frac{-3.2}{7.\left(-1\right)}=\frac{6}{7}\end{matrix}\right.\)
a) \(2x\left(x-\frac{1}{7}\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}2x=0\\x-\frac{1}{7}=0\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x=0:2=0\\x=0+\frac{1}{7}=\frac{1}{7}\end{matrix}\right.\)
b) \(\frac{1}{2}x+\frac{3}{5}x=-\frac{33}{25}\)
\(\Rightarrow x\left(\frac{1}{2}+\frac{3}{5}\right)=-\frac{33}{25}\)
\(\Rightarrow x\frac{11}{10}=-\frac{33}{25}\)
\(\Rightarrow x=\left(-\frac{33}{25}\right):\frac{11}{10}=-\frac{33}{25}.\frac{10}{11}=-\frac{6}{5}\)
c) \(\left(\frac{2}{3}x-\frac{4}{9}\right)\left(\frac{1}{2}+\frac{-3}{7}:x\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}\frac{2}{3}x-\frac{4}{9}=0\\\frac{1}{2}+\frac{-3}{7}:x=0\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}\frac{2}{3}x=0+\frac{4}{9}=\frac{4}{9}\\-\frac{3}{7}:x=0-\frac{1}{2}=-\frac{1}{2}\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x=\frac{4}{9}:\frac{2}{3}=\frac{4}{9}.\frac{3}{2}=\frac{2}{3}\\x=\left(-\frac{3}{7}\right):\frac{-1}{2}=\left(-\frac{3}{7}\right).\left(-2\right)=\frac{6}{7}\end{matrix}\right.\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a)\(0,45-\left|1,3-x\right|=0\)
\(\Leftrightarrow\left|1,3-x\right|=0,45-0\)
\(\Leftrightarrow\hept{\begin{cases}1,3-x=0,45\\1,3-x=-0,45\end{cases}}\)\(\Leftrightarrow\hept{\begin{cases}x=1,3-0,45\\x=1,3+0,45\end{cases}}\)\(\Leftrightarrow\hept{\begin{cases}x=0,85\\x=1,75\end{cases}}\)
Vậy x = 0,85 ; x = 1,75
b) \(\left|3x-5\right|-\frac{1}{7}=\frac{1}{3}\)
\(\Leftrightarrow\left|3x-5\right|=\frac{1}{3}+\frac{1}{7}\)
\(\Leftrightarrow\left|3x-5\right|=\frac{10}{21}\)
\(\Leftrightarrow\hept{\begin{cases}3x-5=\frac{10}{21}\\3x-5=-\frac{10}{21}\end{cases}}\)\(\Leftrightarrow\hept{\begin{cases}3x=\frac{10}{21}+5\\3x=-\frac{10}{21}+5\end{cases}}\)\(\Leftrightarrow\hept{\begin{cases}3x=\frac{115}{21}\\3x=\frac{95}{21}\end{cases}}\)\(\Leftrightarrow\hept{\begin{cases}x=\frac{115}{63}\\x=\frac{95}{63}\end{cases}}\)
Vậy x = .........................
![](https://rs.olm.vn/images/avt/0.png?1311)
1.a) Sửa lại đề: \(\frac{11}{17}\)ở mẫu chuyển thành \(\frac{11}{7}\)
\(\frac{0,75+0,6-\frac{3}{7}-\frac{3}{13}}{2,75+2,2-\frac{11}{7}-\frac{11}{13}}=\frac{\frac{3}{4}+\frac{3}{5}-\frac{3}{7}-\frac{3}{13}}{\frac{11}{4}+\frac{11}{5}-\frac{11}{7}-\frac{11}{13}}\)\(=\frac{3\left(\frac{1}{4}+\frac{1}{5}-\frac{1}{7}-\frac{1}{13}\right)}{11\left(\frac{1}{4}+\frac{1}{5}-\frac{1}{7}-\frac{1}{13}\right)}=\frac{3}{11}\)
( vì \(\frac{1}{4}+\frac{1}{5}-\frac{1}{7}-\frac{1}{13}\ne0\))
2.a) \(\frac{3}{5}+\frac{3}{2}.x=\frac{-5}{7}\)\(\Leftrightarrow\frac{3}{2}.x=\frac{-5}{7}-\frac{3}{5}\)
\(\Leftrightarrow\frac{3}{2}.x=\frac{-46}{35}\)\(\Leftrightarrow x=\frac{-46}{35}:\frac{3}{2}\)\(\Leftrightarrow x=\frac{-92}{105}\)
Vậy \(x=\frac{-92}{105}\)
b) \(\left(4x-\frac{1}{3}\right).\left(\frac{3}{2}x+\frac{5}{6}\right)=0\)\(\Leftrightarrow\orbr{\begin{cases}4x-\frac{1}{3}=0\\\frac{3}{2}x+\frac{5}{6}=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}4x=\frac{1}{3}\\\frac{3}{2}x=\frac{-5}{6}\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=\frac{1}{12}\\x=\frac{-5}{9}\end{cases}}\)
Vậy \(x=\frac{-5}{9}\)hoặc \(x=\frac{1}{12}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left|x-\frac{2}{5}\right|+\frac{1}{2}=\frac{3}{4}\)
=> \(\left|x-\frac{2}{5}\right|=\frac{1}{4}\)
=> \(\orbr{\begin{cases}x-\frac{2}{5}=\frac{1}{4}\\x-\frac{2}{5}=-\frac{1}{4}\end{cases}}\Rightarrow\orbr{\begin{cases}x=\frac{13}{20}\\x=\frac{3}{20}\end{cases}}\)
b) \(\left|5-3x\right|+\frac{2}{3}=\frac{11}{6}\)
=> \(\left|5-3x\right|=\frac{7}{6}\)
=> \(\orbr{\begin{cases}5-3x=\frac{7}{6}\\5-3x=-\frac{7}{6}\end{cases}}\Rightarrow\orbr{\begin{cases}3x=\frac{23}{6}\\3x=\frac{37}{6}\end{cases}}\Rightarrow\orbr{\begin{cases}x=\frac{23}{18}\\x=\frac{37}{18}\end{cases}}\)
c) \(\left|x+\frac{3}{4}\right|-\frac{1}{2}=6^2\)
=> \(\left|x+\frac{3}{4}\right|=36,5\)
=> \(\orbr{\begin{cases}x+\frac{3}{4}=36,5\\x+\frac{3}{4}=-36,5\end{cases}}\Rightarrow\orbr{\begin{cases}x=35,75\\x=-37,25\end{cases}}\)
a) \(\left|x-\frac{2}{5}\right|+\frac{1}{2}=\frac{3}{4}\Leftrightarrow\left|x-\frac{2}{5}\right|=\frac{1}{4}\)\(\Leftrightarrow\orbr{\begin{cases}x-\frac{2}{5}=\frac{1}{4}\\x-\frac{2}{5}=\frac{-1}{4}\end{cases}\Leftrightarrow\orbr{\begin{cases}x=\frac{13}{20}\\x=\frac{3}{20}\end{cases}}}\)
b) \(\left|5-3x\right|+\frac{2}{3}=\frac{11}{6}\Leftrightarrow\left|5-3x\right|=\frac{7}{6}\)\(\Leftrightarrow\orbr{\begin{cases}5-3x=\frac{7}{6}\\5-3x=\frac{-7}{6}\end{cases}\Leftrightarrow\orbr{\begin{cases}3x=\frac{23}{6}\\3x=\frac{37}{6}\end{cases}\Leftrightarrow}\orbr{\begin{cases}x=\frac{23}{18}\\x=\frac{37}{18}\end{cases}}}\)
c) \(\frac{1}{5}-\left|\frac{1}{5}-x\right|=\frac{1}{5}\Leftrightarrow\left|\frac{1}{5}-x\right|=0\Leftrightarrow x=\frac{1}{5}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a, ( 152 +và 2/4 - 148 và 3/8 ) : 0,2 = x : 0,3
=> 33/8 : 1/5 = x : 3/10
=> x : 3/10 = 165/8
=> x = 99/10
b, ( 85 và 7/30 - 83 và 5/18 ) : 2 và 2/3 = 0,01x : 4
=> 88/45 : 8/3 = 0,01x : 4
=> 0,01x : 4 = 11/15
=> 0,01x = 44/15
=> x = 880/3
c, x - 1/ x + 5 = 6/7
=> 7( x - 1 ) = 6( x + 5 )
=> 7x - 7 = 6x + 30
=> 7x - 6x = 7 + 30
=> x = 37
d, x2/6 = 24/25
=> x2. 25 = 6 . 24
=> x2.25 = 144
=> x2 = 144/25
=> x = ( 12/5)2 hoặc x = ( -12/5)
g, x - 3/ x + 5 = 5/7
=> 7( x - 3 ) = 5 ( x + 5 )
=> 7x - 21 = 5x + 25
=> 7x - 5x = 21 + 25
=> 2x = 46
=> x = 23
\(\frac{1}{2}x+\frac{3}{5}x=\frac{-33}{25}\)
\(\Rightarrow\left(\frac{1}{2}+\frac{3}{5}\right)x=\frac{-33}{25}\)
\(\Rightarrow\frac{11}{10}x=\frac{-33}{25}\)
\(\Rightarrow x=\frac{-33}{25}\div\frac{11}{10}\)
\(\Rightarrow x=\frac{-6}{5}\)
Vậy \(x=\frac{-6}{5}.\)
\(\frac{1}{2}.x+\frac{3}{5}.x=\frac{-33}{25}\)
\(\Leftrightarrow x.\left(\frac{1}{2}+\frac{3}{5}\right)=\frac{-33}{25}\)
\(\Leftrightarrow x.\left(\frac{5}{10}+\frac{6}{10}\right)=\frac{-33}{25}\)
\(\Leftrightarrow x.\frac{11}{10}=\frac{-33}{25}\)
\(\Leftrightarrow x=\frac{-33}{25}:\frac{11}{10}=\frac{-33}{25}.\frac{10}{11}\)
\(\Leftrightarrow x=\frac{-330}{275}=\frac{-6}{5}\)